EARNINGS MANAGEMENT AND DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY WITH INDEPENDENT COMMISSIONERS AND INSTITUTIONAL OWNERSHIP AS MODERATING VARIABLES - Carolyn Lukita Sembiring (Berkala Akuntansi dan Keuangan Indonesia, 2017)
This study examines the effect of corporate social responsibility disclosure on earnings management actions. This study also examines the moderating variables, namely the independent board of commissioners and institutional ownership. The population in this study are mining companies listed on the Indonesia Stock Exchange during the study period, because the mining sector is the sector that has the most potential to damage the environment. Regression analysis was used to test the hypothesis. The results show that the overall hypothesis is supported, CSR disclosure is significantly negatively related to earnings management. This shows that if the company discloses broader social accountability (such as CSR disclosure), then earnings management will decline. This study also succeeded in proving that independent commissioners and institutional ownership were proven to strengthen the negative relationship between CSR and earnings management through voting power and more intense supervision which encouraged CSR disclosure and reduced the likelihood of earnings management actions.